Biomechanical factors influencing tumble turn performance of elite female swimmers - Puel, F.; Morlier, J.; Cid, M.; Chollet, D.; Hellard, P. (Biomechanics and Medicine in Swimming XI, 2010)
INTRODUCTION: Turns represent an important factor in determining the final performance of a swimming race. A successful turn results from a multitude of factors. The freestyle tumble turn can be divided into the approach, rotation, wall contact, glide, underwater propulsion, and stroke resumption phases. The aim of this study was to analyse relations with both kinematic and dynamic factors of each phases and the 3mRTT as measure of turning performance. METHODS: Eight elite female swimmers participated in this study (22.3 ± 4.1 years, 62.2 ± 6.2 kg, 174.7 ± 5.8 cm). They were monitored during a crawl tumble turn at maximum speed. 5 stationary video cameras were located underwater on a semi-ellipse centred on the calibrated turn place. An underwater 3D force platform was mounted on the turning wall. Every interesting anatomical reference point was digitized manually at a frequency of 50 Hz. Image coordinates were transformed to 3D object-space coordinates using the DLT algorithm. The principal kinematic data were horizontal velocities of the head (e.g. VGUP at the end of the glide) and the duration of each phase (e.g. glide duration GD). The major dynamic data was the time between the beginning of the push-off and the maximum horizontal force peak (%PFHM in % and PFHM in s). The tumble turn performance criterion (PERF) was the time taken to swim from 3 m in to 3 m out the turning wall (3mRTT in s). RESULTS: High correlation coefficients values were observed between PERF and %PFHM (r = 0.84, p = 0.017), PFHM (r = 0.82, p = 0.024) and GD (r = 0.79, p = 0.035). The best model was PERF = 0.741 x %PFHM + 0.842 x GD + 0.334 x VGUP + 1.532 (F = 49.9, r²adj = 0.95, p = 0.001). PFHM explained 80 % of PERF, GD explained 12 % and VGUP 3 %. DISCUSSION: The major result of this study was that best female swimmers were able to develop soon her maximal horizontal force during the push-off phase. The time of peak force and the glide phase were preponderant. Further studies with an extended population (elite male and less-skilled female swimmers) would analyse the effects of more dynamic factors.